Real-time noise cancelling approach on innovations-based whitening application to adaptive FIR RLS in beamforming structure - Jeong, Jinsoo (Intech, 2011)
The techniques for noise cancellation have been developed with applications in signal processing, such as homomorphic signal processing, sensor array signal processing and statistical signal processing. Some exemplar applications may be found from kepstrum (also known as complex ceptstrum) method, beamforming and ANC (adaptive noise cancelling).